The biological function of antibodies induced by the RTS, S/AS01 malaria vaccine candidate is determined by their fine specificity. (December 2016) - Chaudhury, Sidhartha; Ockenhouse, Christian; Regules, Jason; Dutta, Sheetij; Wallqvist, Anders; Jongert, Erik; Waters, Norman; Lemiale, Franck; Bergmann-Leitner, Elke
Abstract Background Recent vaccine studies have shown that the magnitude of an antibody response is often insufficient to explain efficacy, suggesting that characteristics regarding the quality of the antibody response, such as its fine specificity and functional activity, may play a major role in protection. Previous studies of the lead malaria vaccine candidate, RTS, S, have shown that circumsporozoite protein (CSP)-specific antibodies and CD4+ T cell responses are associated with protection, however the role of fine specificity and biological function of CSP-specific antibodies remains to be elucidated. Here, the relationship between fine specificity, opsonization-dependent phagocytic activity and protection in RTS, S-induced antibodies is explored. Methods A new method for measuring the phagocytic activity mediated by CSP-specific antibodies in THP-1 cells is presented and applied to samples from a recently completed phase 2 RTS, S/AS01 clinical trial. The fine specificity of the antibody response was assessed using ELISA against three antigen constructs of CSP: the central repeat region, the C-terminal domain and the full-length protein. A multi-parameter analysis of phagocytic activity and fine-specificity data was carried out to identify potential correlates of protection in RTS, S. Results Results from the newly developed assay revealed that serum samples from RTS, S recipients displayed a wide range of robust and repeatable phagocytic activity. Phagocytic activity was correlated with full-length CSP and C-terminal specific antibody titres, but not to repeat region antibody titres, suggesting that phagocytic activity is primarily driven by C-terminal antibodies. Although no significant difference in overall phagocytic activity was observed with respect to protection, phagocytic activity expressed as 'opsonization index', a relative measure that normalizes phagocytic activity with CS antibody titres, was found to be significantly lower in protected subjects than non-protected subjects. Conclusions Opsonization index was identified as a surrogate marker of protection induced by the RTS, S/AS01 vaccine and determined how antibody fine specificity is linked to opsonization activity. These findings suggest that the role of opsonization in protection in the RTS, S vaccine may be more complex than previously thought, and demonstrate how integrating multiple immune measures can provide insight into underlying mechanisms of immunity and protection.